Cas12a-assisted precise targeted cloning using in vivo Cre-lox recombination - Behnam Enghiad (Nature Portfolio, 2021)
Direct cloning of biosynthetic gene clusters is difficult due to their size and repetitive nature. Here, the authors present CAPTURE, which uses Cas12a and in vivo Cre-lox recombination for efficient cloning of gene clusters up to 113 kb, and demonstrate how this method can be used for large-scale discovery of novel natural products.